Sing [videorecording (Blu-Ray)] - Jennings, Garth; Talbot, Joby (Universal Pictures Home Entertainment, 2017)
A koala impresario stages a grand singing competition for the world's animals in order to save his elegant theater and bring it back to its former glory.